ANTENATAL CARE IN THE PERSPECTIVE OF PREGNANT WOMEN IN THE VILLAGE OF BANDAR SETIA, DELI SERDANG REGENCY - Riska Susanti Pasaribu; Ida Yustina; Nurmaini Nurmaini; Kintoko Rochadi; Fikarwin Zuska (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Antenatal care is care for the mother and fetus during pregnancy. How important are antenatal care visits Very important. Through antenatal care various information and education related to pregnancy and childbirth preparation can be given to mothers as early as possible. The number of MMR in Deli Serdang Regency has continued to decrease since 2015. In 2020 the number of maternal deaths in Deli Serdang Regency is 12 people per 44,298 live births. There are several factors that cause maternal death in Deli Serdang Regency, including: 6 (six) due to bleeding cases, due to infection in 1 (one) case and other consequences there were 5 (five) cases such as genetic disease, amniotic fluid embolism, placenta previa and supect COVID-19. This was a qualitative research with a narrative approach. The research was conducted in Bandar Setia Village, Deli Serdang Regency. The respondents in this study were pregnant women who live in Bandar Setia Village who were taken by purposive sampling, namely the selection of respondents was carried out deliberately according to their needs. So that the total respondents in this study were 17 people. Data collection techniques were carried out by interviews and FGD (Focus Group Discussion). The number of pregnant women were 17 people with a gestational age of 20-40 weeks. The results of the study revealed that all pregnant women gave a complete and clear explanation of their opinion about prenatal visits or antenatal care and explained in detail about their respective experiences during pregnancy, the perceived obstacles as the reason for not carrying out prenatal visits or antenatal care. Therefore, pregnant women say in detail what are the obstacles or problems as the main cause so that pregnancy visits cannot be carried out in accordance with government recommendations, namely at least 6 visits during pregnancy.